Biopsychosocial model in psychiatry: an anthropo-synergistic view of the problem (Report №1) - V. A. Abramov; V. V. Melnichenko; E. V. Babura (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article is devoted to the problem of the identity of psychiatry as a medical science in the descriptive categories of biological reductionism and humanitarian-anthropological approach. The positive and negative aspects of the use of biomedical principles of evidence-based medicine in psychiatric discourse are presented. The importance of cognition of a person as a synergistic (holistic) reality is emphasized, taking into account scientific prejudices. A systematic holistic description of pathokinesis and the content of a mental disorder is given through the study of the emergent qualities of a personality and its potential. The features of various types of biopsychosocial models are given, which, in the opinion of their adherents, provide a systematic approach to the relationship of the biological substrate (the brain) with mental phenomena and social behavior.